Cerebral Venous Sinus Thrombosis: Unusual Clot-Forming Phenomenon Post Head Trauma - Siew Im Khoo; Mohamed Micdhadhu, Mohamed Azlam B.; Tan, Seu Kean; Irene Looi (Journal Of Cardiovascular, Neurovascular & Stroke, 2024)
Introduction/ Background: Cerebral venous sinus thrombosis (CVST) is commonly seen in daily practice, especially in those with predisposing factors. Clinicians might miss the diagnosis if there is a low index of suspicion during clinical assessment of head injury cases, particularly in those without the risk factor. Case Report: We report a case of a post-traumatic head injury with skull fracture and subarachnoid haemorrhage complicated with delayed, countercoup cerebral venous sinus thrombosis in the context of no predisposing factor for thrombosis. He was started on anticoagulant and achieved clinical improvement within a week. Discussion: CVST is seen in post head trauma patients regardless of severity of the injury. Presence of neurological deficit post head injury like altered mental status, headache, vomiting or focal neurological signs like hemiparesis raised the suspicious of CVST. Occurrence of CVST can be delayed up to more than 10 days post trauma and it can happen at the opposite site of the trauma. Conclusion: High suspicion index is needed to diagnose CVST early and subsequently early intervention or treatment could improve clinical outcome and prognosis of the patients.